2022
DOI: 10.1002/cbic.202200536
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Photophysical Properties and Biological Evaluation of New Conjugates BODIPY: Dinuclear Trithiolato‐Bridged Ruthenium(II)‐Arene Complexes

Abstract: The synthesis, photophysical properties and antiparasitic efficacy against Toxoplasma gondii β-gal (RH strain tachyzoites expressing β-galactosidase) grown in human foreskin fibroblast monolayers (HFF) of a series of 15 new conjugates BODIPYtrithiolato-bridged dinuclear ruthenium(II)-arene complexes are reported (BODIPY = 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene, derivatives used as fluorescent markers). The influence of the bond type (amide vs. ester), as well as that of the length and nature (alkyl vs. ary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 104 publications
1
19
0
Order By: Relevance
“…Noteworthy, TEM (transmission electron microscopy) studies of different protozoan parasites ( Toxoplasma gondii , Neospora caninum , Trypanosoma brucei ) treated with trithiolato dinuclear ruthenium(II)-arene complexes revealed alterations in the mitochondrial ultrastructure pointing out this organelle as a potential target [ 89 ]. Interestingly, a similar effect was also observed in the case of trithiolato diruthenium conjugates with coumarin and BODIPY fluorophores [ 93 , 94 ].…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Noteworthy, TEM (transmission electron microscopy) studies of different protozoan parasites ( Toxoplasma gondii , Neospora caninum , Trypanosoma brucei ) treated with trithiolato dinuclear ruthenium(II)-arene complexes revealed alterations in the mitochondrial ultrastructure pointing out this organelle as a potential target [ 89 ]. Interestingly, a similar effect was also observed in the case of trithiolato diruthenium conjugates with coumarin and BODIPY fluorophores [ 93 , 94 ].…”
Section: Resultssupporting
confidence: 57%
“…Compounds 7 , 14 , and 30 have an ester linker that can potentially be hydrolyzed in growth media. Comparable conjugates with coumarin and BODIPY fluorescent units linked through ester bonds to the diruthenium unit were recently investigated [ 93 , 94 ]. As a very limited solvolysis of the ester bonds was noticed after 168 h for some compounds, it was concluded that the coumarin and BODIPY diruthenium conjugates exhibit high stability in the conditions used for the biological evaluations [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of the trithiolato diruthenium complexes is generally straightforward and efficient [90][91][92], and this scaffold is robust to chemical modification and easily adaptable to the conjugate strategy as demonstrated by the various series of hybrids with peptides [93], drugs [94,95], fluorophores [92] , [96] or metabolites [97]. Ester and amide couplings [92,98], but also CuAAC (Cu(I)catalyzed azide-alkyne cycloaddition) click reactions [95] , [97] proved to be useful tools for the functionalization of the diruthenium trithiolato unit at the level of the bridge thiols.…”
Section: Figurementioning
confidence: 99%
“…For determination of IC50 on T. gondii β-gal, eight serial concentrations ranging from 7 nM to 1 μM were tested for each selected compound as previously described [92,95,96].…”
Section: Ic50 Determinationmentioning
confidence: 99%